234k views
0 votes
Evaluate the expressiin when a=6, b=3, and c=2: c(b+a)-a= please help

1 Answer

1 vote

Answer:


\huge{ \fbox{ \tt{12}}}

Explanation:


\underline{ \sf{Given}} : \sf a=6, \: b=3 \: and \: c=2


\underline{ \sf{To \: find }} : \sf{Value \: of \: the \: given \: expression}


\underline{ \underline{ \mathfrak{Let's \: solve}}} :


\bigstar{ \tt{ \: c \: ( \: b \: + \: a \: ) - \: a}}


\text{Step \: 1 \: } : Plug the values of a , b and c


\mapsto{ \tt{ \: 2 \: ( \: 3 \: + \: 6 \: ) \: - \: 6}}


\text{Step \: 2} : \sf{ \: Add \: the \: numbers : 6 \: and \: 3}


\mapsto{ \sf{ \: 2 \: * \: 9 \: - \: 6 \: }}


\text{Step \: 3 \: } : \sf{ \: Multiply \: the \: numbers : 9 \: and \: 2}


\mapsto{ \sf{18 - 6}}


\text{Step \: 4 \:} : \sf{Subtract \: 6 \: from \: 18}


\mapsto{ \sf{ \: 12}}

Note : Just follow the PEMDAS rule ( See attached picture )

Hope I helped!

Best regards! :D

~
\sf{TheAnimeGirl}

Evaluate the expressiin when a=6, b=3, and c=2: c(b+a)-a= please help-example-1
User Ganessa
by
4.8k points